Histological and Morphometric Analysis with Grading of Atherosclerosis-Associated Myocardial Changes in Cases of Sudden Death at a Tertiary Care Hospital - Prathana Patel; Smita Jhaveri; Parth Patel (National Journal of Medical Research)
Background: Sudden cardiac death (SCD) remains a significant public health concern worldwide, representing a considerable proportion of mortality linked to cardiovascular diseases. Atherosclerosis, a progressive disease characterized by the accumulation of lipids, fibrous elements, and inflammatory cells within the arterial walls, is a leading underlying cause of SCD.